2019
DOI: 10.1002/jmv.25600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver failure in a pediatric transplant recipient of a liver allograft with inherited chromosomally integrated HHV‐6B

Abstract: Background Active infections of human herpesvirus 6B (HHV‐6B) are frequent in immunocompromised recipients after transplantation. Nevertheless, they need to be distinguished from latent inherited chromosomally integrated genomes (iciHHV‐6) present in about 1% of the population to avoid unnecessary administration of toxic antivirals. Methods A 5‐year‐old child presented with acute liver allograft rejection associated with HHV‐6 DNA in plasma, which led to an unfavorable outcome. We investigated the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In immunosuppressed patients, reactivated HHV-6 from iciHHV-6 can induce acute liver failure and acute rejection, as demonstrated in a 5-year transplant recipient, by the presence of mRNA and late viral protein in the sole iciHHV-6B+ liver allograft [31]. Reactivated HHV-6 from iciHHV-6 is susceptible to antiviral drugs and can be treated with ganciclovir, valganciclovir, cidofovir, brincidofovir, or foscarnet [28,[31][32][33][34]. However, antiviral treatment, considered a therapeutic option for iciHHV-6-associated diseases, leads to variable clinical improvement [24,33,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In immunosuppressed patients, reactivated HHV-6 from iciHHV-6 can induce acute liver failure and acute rejection, as demonstrated in a 5-year transplant recipient, by the presence of mRNA and late viral protein in the sole iciHHV-6B+ liver allograft [31]. Reactivated HHV-6 from iciHHV-6 is susceptible to antiviral drugs and can be treated with ganciclovir, valganciclovir, cidofovir, brincidofovir, or foscarnet [28,[31][32][33][34]. However, antiviral treatment, considered a therapeutic option for iciHHV-6-associated diseases, leads to variable clinical improvement [24,33,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the highest levels of gene expression in the T-cells, brain, testis, esophagus, and adrenal gland, it has been demonstrated that ciHHV-6B is able to reactivate in hepatocytes as a permissive cell [27,30]. In immunosuppressed patients, reactivated HHV-6 from iciHHV-6 can induce acute liver failure and acute rejection, as demonstrated in a 5-year transplant recipient, by the presence of mRNA and late viral protein in the sole iciHHV-6B+ liver allograft [31]. Reactivated HHV-6 from iciHHV-6 is susceptible to antiviral drugs and can be treated with ganciclovir, valganciclovir, cidofovir, brincidofovir, or foscarnet [28,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of ciHHV‐6 is vital for clinical strategy. ciHHV‐6–induced HHV‐6 infection after liver transplant has been reported to be associated with liver rejection and mortality 15,16 . On the other hand, misdiagnosis of ciHHV‐6 as HHV‐6 reactivation will result in unnecessary and potentially toxic antiviral therapy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the presence of a large viral genome within a telomere has been shown to cause localized instability that may influence telomere DNA damage signaling and function ( Huang et al, 2014 ; Wood and Royle, 2017 ; Zhang et al, 2016 ). Recent studies have also indicated an association between iciHHV-6A/6B and angina pectoris ( Gravel et al, 2015 ); unexplained infertility ( Miura et al, 2020 ); an increased risk of aGVHD following hematopoietic stem cell transplantation when either the donor or recipient has iciHHV-6A/6B ( Hill et al, 2017 ; Weschke et al, 2020 ); complications following solid organ transplantation when there was iciHHV-6A/6B donor/recipient mismatch ( Bonnafous et al, 2018 ; Bonnafous et al, 2020 ; Petit et al, 2020 ); and possibly an increased risk of pre-eclampsia ( Gaccioli et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%